PROBLEMS OF SYRIAN REFUGEES AND REFLECTIONS TO TURKEY - KÖYÜSTÜ, Sevda; MEHEL TUTUK, S. Pınar (Atlas Journal, 2018)
The on going conflicts and wars in different parts of the world on different dates forced millions of people to migrate. The civil war in Syria affects not only Syria but many other countries from economic, social and societal aspects. Many families had to migrate due to the reasons such as the war and the negative living conditions and survival concerns caused from that war. The process which started in Tunisia for the first time as a consequence of burning genocide on December 17, 2010, and which was called Arab Spring, continued in Egypt, Libya and Syria. Especially, Turkey was affected by the Arab Spring in Syria. Coming this point, the number of refugees in Turkey is estimated that nearly 4 million. Along with the increasing number of Syrians, various problems have occurred in terms of economic, cultural, education and health. The main purpose of this study is; examine the problems faced by refugees in Syria and Turkey to assess the implications of it. In the study conducted through the literature review, the problems of the Syrian refugees were addressed in four sections (* housing and basic needs, ** education, *** health, **** economics) and interpretation of the reflection of them.